2013
DOI: 10.1007/s00344-013-9352-6
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin Differences in In Vitro Cultures and Inflorescences from Normal and Mantled Oil Palm (Elaeis guineensis Jacq.)

Abstract: The mantled abnormality phenotype of the oil palm affects fruit development and thus jeopardizes oil yield. Cytokinins have been implicated in the development of the mantled phenotype. Endogenous cytokinin levels in the normal and mantled phenotypes were compared to determine whether levels of specific cytokinins are associated with mantling. Endogenous cytokinins were identified and quantified in in vitro cultures and inflorescences from normal and mantled oil palms. Twenty-two isoprenoid cytokinins, comprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
(11 reference statements)
0
4
0
2
Order By: Relevance
“…Eeuwens et al (2002) observed that, in general, a relatively high auxin/cytokinin ratio resulted in the lowest incidence of variant ‘mantled’ flowering in oil palm, while using media supplemented with relatively high cytokinins/auxin ratio resulted in a high incidence of mantled flowering. The role of cytokinin was further confirmed by Ooi et al (2013), who noticed that the mantled inflorescences of oil palm contained higher levels of cytokinins like isopentenyladenine 9-glucoside and lower levels of trans-zeatin 9-glucoside, dihydrozeatin riboside, and dihydrozeatin riboside 5′-monophosphate compared with normal inflorescences.…”
Section: Sources Of Variations Detected In Plant Tissue Culturementioning
confidence: 68%
“…Eeuwens et al (2002) observed that, in general, a relatively high auxin/cytokinin ratio resulted in the lowest incidence of variant ‘mantled’ flowering in oil palm, while using media supplemented with relatively high cytokinins/auxin ratio resulted in a high incidence of mantled flowering. The role of cytokinin was further confirmed by Ooi et al (2013), who noticed that the mantled inflorescences of oil palm contained higher levels of cytokinins like isopentenyladenine 9-glucoside and lower levels of trans-zeatin 9-glucoside, dihydrozeatin riboside, and dihydrozeatin riboside 5′-monophosphate compared with normal inflorescences.…”
Section: Sources Of Variations Detected In Plant Tissue Culturementioning
confidence: 68%
“…Tissue culture through somatic embryogenesis is an attractive alternative to massively propagate elite genotypes of oil palm (Ooi et al, 2013). Nevertheless, the efficiency of plan regeneration is strongly associated with the chosen type of explant.…”
Section: Discussionmentioning
confidence: 99%
“…For clonal multiplication of oil palm, the somatic embryogenesis has been the most used method (Konan et al, 2006;Ong-Abdullah et al, 2015;Ooi et al, 2013;Palanyandy et al, 2013), and it has already been tested from different explants, such as immature leaves of young plants, immature inflorescences and zygotic embryos (Balzon et al, 2013;Yusnita and Hapsoro, 2011;Rajesh et al, 2003;Scherwinsky-Pereira et al, 2010;Thuzar et al, 2011). It is important to highlight that details for clonal multiplication of oil palm are not published, since researches are conducted by companies with commercial interests, not interested in providing their protocols (Scherwinsky-Pereira et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Analisis kuantitatif sitokinin yang terkandung di dalam eksplan dibutuhkan untuk memonitor tingkat konsentrasi sitokinin pada fase-fase perkembangan kultur seperti misalnya pada kalus atau embrio. Ooi et al (2013) melaporkan bahwa total level konsentrasi sitokinin meningkat secara bertahap seiring fase perkembangan kultur pada kultur in vitro kelapa sawit asal klon normal dan mantel. Level sitokinin juga cenderung rendah pada tahap kalogenesis dan pemberian auksin secara eksternal untuk menstimulasi embriogenesis mungkin menekan biosintesis sitokinin (Moubayidin et al, 2009).…”
Section: Pendahuluanunclassified